PEMANFAATAN LIMBAH ORGANIK DENGAN PENAMBAHAN BIOFUND UNTUK MENINGKATKAN PRODUKSI TANAMAN JAGUNG (Zea mays L.) - Murdaningsih Murdaningsih (Agriculture Faculty of Flores University, 2009)
Organic waste comes from pigswill livestock can used as a plant nutrient source. Organic material has a significant influence on agriculture productivity. Organic material added continually was an effective way to maintain soil health, it will provide soil organisms food, increasing available nutrient and maintain soil physic characteristic. Otherwise, organic waste added still not get an optimal result. That's why organic waste added from pigswill livestock and bio fund as activator was one of the alternative ways. This study was aimed to know pigswill livestock waste potential as organic material added on nutrient availability in order to improve plant productivity and the influence on plant production. This study consisted of two stages; i.e. the first study was soil incubation for 20 days, and the second was maize plant application. The method used was Complete Factorial Randomized design with 2 factors and 3 replicates. The results showed that pigswill livestock organic waste and bio fund will increase soil C, N, P, and K exchange. It happened especially on FIBl and F1B3 treatment; it marks with the increasing trend on every week. The highest production was found on F1B3 (256.63 plants